Impact of "Evaluating Software Complexity Measures" - Weyuker, Elaine J. (IEEE transactions on software engineering, 2025)
We investigate the impact that the paper "Evaluating Software Complexity Measures" has had over the thirty-six year period since it was first published in 1988. We look both at how the frequency of citation increased, and the ways that the research has been used. We describe how citations evolved from the initial obvious intent of assessing newly proposed complexity measures to assessing qualities other than complexity, to using them to assess complexity in entities other than software code, or restricted types of programming paradigms, to the adoption of our approach or properties in fields distinct from computing.